1993
DOI: 10.1042/cs0850343
|View full text |Cite
|
Sign up to set email alerts
|

1H-Nuclear Magnetic Resonance Studies of Human Synovial Fluid in Arthritic Disease States as An Aid to Confirming Metabolic Activity in the Synovial Cavity

Abstract: 1. A 1H-n.m.r. method was used to measure concentrations of valine, alanine, lactate, acetate, hyaluronan and lipids in synovial fluid obtained, during the normal course of examination from the knee joints of patients attending rheumatology and orthopaedic clinics. Fluid was available from 16 patients with osteoarthritis, 18 patients with rheumatoid arthritis, four patients with meniscal tear and one patient each with systemic lupus erythematosis, mono-arthritis, synovitis and loose bodies. Four normal specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 6 publications
0
17
0
1
Order By: Relevance
“…Of those, we found that only HAS2 mRNA was expressed in bovine articular chondrocytes [15]. Increased concentrations of HA have been found at sites of chronic infl ammation [16], and the antioxidative effect of HA has recently been reported [17,18]. The purpose of the present study was to determine if hypoxia induces HA synthesis by chondrocytes, and, if so, whether the hypoxia-induced HA synthesis is regulated by NO.…”
Section: Introductionmentioning
confidence: 90%
“…Of those, we found that only HAS2 mRNA was expressed in bovine articular chondrocytes [15]. Increased concentrations of HA have been found at sites of chronic infl ammation [16], and the antioxidative effect of HA has recently been reported [17,18]. The purpose of the present study was to determine if hypoxia induces HA synthesis by chondrocytes, and, if so, whether the hypoxia-induced HA synthesis is regulated by NO.…”
Section: Introductionmentioning
confidence: 90%
“…Increased concentrations of HA have been found at sites of chronic inflammation (20,21), and when the size of this HA has been studied the molecular weight range has been found to include lower molecular weight species (22,23). Chronically inflamed tissues also contain elevated levels of the soluble, chemotactic cytokines known as chemokines (24 -31), many of which are major products of activated macrophages.…”
Section: Nitric Oxide (No ⅐ )mentioning
confidence: 99%
“…Our results showed that the enhanced HA concentration with cyclic strain was due to an increase of HAS2 in the chondrocytes. Increased concentrations of HA have been found at sites of chronic inflammation (27), and lower molecular weight species of HA were exhibited in synovial fluid in arthritis (28). HA has numerous roles in the activation and modulation of the inflammatory response, including the antioxidant scavenging of ROS derived from polymorphonuclear leukocytes (29).…”
mentioning
confidence: 99%